Youth with type 2-diabetes: clinical findings at onset and impact of continuous glucose monitoring (CGM) on glycemic control and disease management - Rosa Thielemann; Lorenz Greifoner; Marlene Dieke; Nicole Kuplin; Kerstin Placzek; Andreas Wienke; Susann Weihrauch-Blüher (Journal of Pediatric Endocrinology and Metabolism, 2026)
Abstract Objectives The global obesity pandemic is associated with a higher prevalence of youth-onset type 2 diabetes (T2D). Continuous glucose monitoring (CGM) is established in type 1 diabetes, however, evidence regarding its impact in pediatric T2D is limited. This study has analyzed (a) clinical and metabolic characteristics in adolescents at T2D onset and (b) the impact of CGM on glycemic control, patient satisfaction and disease management in youths with T2D. Methods a) Clinical and biochemical parameters at diagnosis were assessed in adolescents with T2D. b) The impact of 8 weeks of CGM on HbA 1c , time in range (TIR), markers of the Metabolic Syndrome (MetS), lifestyle and treatment satisfaction were exploratively examined in a subgroup. HbA 1c was subsequently monitored for 12 months. Results Study a): Between 2018 and 2024, 24 adolescents were diagnosed with T2D (25 % female; 14 ± 3 years; HbA 1c : 9.9 ± 2.9 %). Symptoms included polydipsia (45.8 %), polyuria (33.3 %), features of the MetS (100 %), ketoacidosis (16.7 %). Study b): 11 patients participated in the CGM study (14 ± 3 years). After 8 weeks, HbA 1c significantly decreased from 6.9 ± 1.1 to 6.4 ± 0.7 %, TIR increased from 78.5 ± 30.3 % to 87.1 ± 17.6 %. More frequent glucose monitoring was reported by 91 %, more appropriate responses to glucose fluctuations by 82 %, improved quality of life and dietary habits by 73 %. Ninety one percent of participants preferred CGM over capillary testing. HbA 1c remained stable at 6 months (6.4 ± 0.9 %) but increased to 6.9 ± 1.8 % at 12 months after discontinuation of CGM. Conclusions In youth-onset T2D, CGM may improve glycemic outcomes and disease management/quality of life. Larger studies are required.